Measurements of power transformers winding frequency response using the SFRA (Sweep Frequency Response Analysis) method - examples after failures in power transformers and factors that have influence on the recorded frequency responses - Milić, Momčilo; Jovanovic, Djordje; Dimitrijevic, Marko (Proceedings, Electrical engineering institute "Nikola Tesla", 2025)
Sweep Frequency Response Analysis (SFRA) represents an unconventional method used in case of recording the frequency response of transformer windings. The method has found application in the analysis of geometry of power transformer windings in order to determine integrity of the core and winding geometry. Recently, this method has become an almost indispensable part of factory acceptance tests of transformers. Frequency responses recorded in factory or first time in transformer life are used as „fingerprint“ for all future comparisons. The method is applied in on-site tests when mechanical failures are suspected due to the action of dynamic forces during operation, as well as during the transport of transformers. In addition, it can also indicate certain electrical failures. The paper will present examples of recorded frequency responses on transformers that had some failures during their operation. Also it will be shown some examples of various influences on the frequency responses which can be misinterpreted and lead to an error in the assessment of the state of the winding geometry.